2013
DOI: 10.1080/09540121.2013.869540
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and factors associated with willingness to receive short messages for improving antiretroviral therapy adherence in China

Abstract: This study aimed to understand the acceptability of short message service (SMS) as a reminder for improving antiretroviral therapy (ART) adherence and determine the factors associated with willingness to accept SMS among people living HIV (PLH) in China. A total of 801 adult patients were recruited in a cross-sectional survey. Factors associated with willingness in unadjusted analyses (α = 0.10) were included in a logistic regression model; 88.4% of the participants owned mobile phones, 49.6% read every short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
5
12
2
Order By: Relevance
“…Those with education attainment above ordinary level (Form 4) (OR=2.2; p=0.13) were more likely to report a willingness to receive SMS reminders. These findings are consistent with what was reported by Xiaoab et. al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Those with education attainment above ordinary level (Form 4) (OR=2.2; p=0.13) were more likely to report a willingness to receive SMS reminders. These findings are consistent with what was reported by Xiaoab et. al.…”
Section: Discussionsupporting
confidence: 94%
“…38 Client satisfaction is a determinant of treatment uptake, adherence and retention, and an important health systems outcome. 34,35,36 Therefore, dissatisfaction with antiretroviral services could threaten attainment of anti-retroviral treatment objectives. 37 The provider needs to gain the confidence and trust of the client.…”
Section: Discussionmentioning
confidence: 99%
“…Across multiple HIV clinics in Vietnam, 85% of patients used mobile phones, 79% found cell phone reminders an effective adherence aid, and 64 % expressed willingness-to-use the service with an average willingness-to-pay of $2.50 per month (Tran & Houston, 2012). In a cross-sectional survey of 801 Chinese people living with HIV, 88% of the participants owned mobile phones and 80% felt daily text reminders to take medication would be helpful (Xiao et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…A large (N=301) study of caregivers of children with HIV in Cameroon (an acceptability study for the MORE CARE mHealth trial) similarly found high acceptability of SMS reminders for appointments [43]. Finally, a survey-based study from China found that SMS reminders would be acceptable and that, among other factors, participants who were younger and more highly educated were more accepting of the intervention [44].…”
Section: Uptake/acceptabilitymentioning
confidence: 86%